Probiotics improve symptoms of patients with COVID-19 through gut-lung axis: a systematic review and meta-analysis - Tian, Yong; Ran, Hongmei; Wen, Xudong; Fu, Guochuan; Zhou, Xiaofang; Liu, Rui; Pan, Tao (Frontiers in Nutrition, 2023)
Background Multi system symptoms such as gastrointestinal tract and respiratory tract exist in coronavirus disease 2019 (COVID-19) patients. There is a lack of reliable evidence to prove that probiotics are effective in improving these symptoms. In this study, we aimed to evaluate the efficacy of probiotics in meta-analysis. Methods We systematically searched PubMed, Embase, Web of Science, and Cochrane Library up to February 15, 2023. Randomized controlled trials or high quality retrospective studies comparing the efficacy of probiotics as supplementation with non-probiotics in improving symptoms for patients with COVID-19 were included. This meta-analysis assessed endpoints using Review Manager 5.3. Result Ten citations comprising 1198 patients with COVID-19 were included. The results showed that probiotics could increase the number of people with overall symptom improvement (RR = 1.62, 95% CI [1.10, 2.38], P = 0.01) and shorten the duration (days) of overall symptoms (MD = −1.26, 95% CI [−2.36, −0.16], P = 0.02). For the duration (days) of specific symptoms, probiotics could improve diarrhea (MD = −2.12, 95% CI [−2.41, −1.83], P < 0.00001), cough (MD = −2.21, 95% CI [-4.56, 0.13], P = 0.06) and shortness of breath (MD = −1.37, 95% CI [-2.22, −0.53], P = 0.001). Probiotics had no obvious effect on fever, headache and weakness. For inflammation, probiotics could effectively reduce C-reactive Protein (CRP) serum level (mg/L) (MD = −4.03, 95% CI [−5.12, −2.93], P < 0.00001). Regarding hospital stay (days), probiotics group was shorter than non-probiotics group (MD = −0.98, 95% CI [−1.95, −0.01], P = 0.05). Conclusion To some extent probiotics could improve the overall symptoms, inflammatory reaction and shorten hospital stay of patients with COVID-19. Probiotics may improve gastrointestinal symptoms (such as improving intestinal flora and reducing the duration of diarrhea) and further improve respiratory symptoms through the gut-lung axis. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=398309, identifier: CRD42023398309.